2018
DOI: 10.1084/jem.20170934
|View full text |Cite
|
Sign up to set email alerts
|

The Cdx2 homeobox gene suppresses intestinal tumorigenesis through non–cell-autonomous mechanisms

Abstract: Balbinot et al. show that intestinal epithelial cells depleted in the homeobox gene Cdx2 acquire an imperfect gastric-type metaplastic phenotype that, through changes in the microenvironment, induces the tumorigenic evolution of adjacent Cdx2-intact cells without themselves becoming cancerous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 51 publications
(82 reference statements)
3
50
0
Order By: Relevance
“…Strong CDX2 down-regulation was shown to be associated with one particular subtype characterized by serrated precursor neoplasia, stromal infiltration, stem-cell–like features, and poor prognosis (Marisa et al, 2013). In the current mouse study, Balbinot et al (2018) found the expected, cecal polypoid lesions with some degree of gastric metaplasia. This was confirmed by transcriptomic analysis where intestinal markers such as Cdx1 or Alpi were down-regulated and several gastric markers (e.g., Tff1/2, Cldn18, Muc1/6) were up-regulated.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Strong CDX2 down-regulation was shown to be associated with one particular subtype characterized by serrated precursor neoplasia, stromal infiltration, stem-cell–like features, and poor prognosis (Marisa et al, 2013). In the current mouse study, Balbinot et al (2018) found the expected, cecal polypoid lesions with some degree of gastric metaplasia. This was confirmed by transcriptomic analysis where intestinal markers such as Cdx1 or Alpi were down-regulated and several gastric markers (e.g., Tff1/2, Cldn18, Muc1/6) were up-regulated.…”
supporting
confidence: 60%
“…In the search for a mechanism, Balbinot et al (2018) looked again at the transcriptome of gastric metaplasia present in the cecum. They found up-regulation of several cytokines and chemokines previously associated with malignancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation might implicate Paneth cells as an origin for the formation of UACL, but this requires further investigation. Of note, loss of Cdx2 in the intestines of mice leads to the development of a pyloric-type metaplasia expressing antral mucins, TFF1, and TFF2 [64,65]. Thus, loss of the expression of the Cdx2 master-regulator transcription factor in stem cells may also account for colonic lineage reprogramming towards an antral mucous gland phenotype.…”
Section: Lineage Origins Of Pyloric-type Reparative Mucous Cellsmentioning
confidence: 99%
“…Maf factors are involved in the cell stress response and can interact alternatively with Bach or Nfe to promote transcription repression or activation 36 . It is also interesting that expression of the homeobox gene Cdx2 and the nuclear receptor family gene Hnf4α, two major regulators of intestinal homeostasis with tumour suppressor activity 37 39 , was downregulated, as well as stimulation of the Macc1 gene involved in metastasis 40 .
Figure 8 Functional clustering annotation of the differentially expressed genes.
…”
Section: Adaptation With Changes In the Gene Expression Profilementioning
confidence: 99%